Miniaturized microwave bandpass filter based on modified hairpin topology - Srisathit, K.; Tangjit, J.; Surakampontorn, W. (My University, 2010)
This paper presents a microstrip hairpin bandpass filter (BPF) with simultaneously compact size and harmonic suppression. With the use of a square groove technique, the phase velocities between even- and odd-mode in parallel-coupled line segment are compensated. Two prototype filters based on the conventional hairpin and the proposed hairpin BPF are designed at the center frequency of 2.45 GHz with a fractional bandwidth of 20 percentages and fabricated on the microstrip structure. The proposed BPF exhibits the measured insertion loss of 1.2 dB at the centered frequency of 2.49 GHz, whereas the in-band return loss is kept below 12 dB from 2.21 to 2.7 GHz. Good agreements between the simulation and measurement can be obtained. © 2010 IEEE.
Keywords: Compact size; Groove; Hairpin filter; Harmonic suppression; Phase velocity